Constipation in parkinson's disease: Subjective symptoms, objective markers, and new perspectives. Issue 1 (22nd November 2016) - Knudsen, Karoline; Krogh, Klaus; Østergaard, Karen; Borghammer, Per
ABSTRACT: Constipation is among the first nonmotor symptoms to develop in the prodromal phase of PD. Pathological alpha‐synuclein deposition is present throughout the gastrointestinal tract up to 20 years preceding diagnosis. Nevertheless, constipation in the context of PD remains ill defined and poorly understood. In this review, we summarize current knowledge of subjective symptoms and objective measures of constipation in PD. More than 10 different definitions of constipation have been used in the PD literature, making generalizations difficult. When pooling results from the most homogeneous studies in PD, a median constipation prevalence of 40% to 50% emerges, but with large variation across individual studies. Also, constipation prevalence tends to increase with disease progression. A similar prevalence is observed among patients with idiopathic rapid eye movement sleep behavior disorder. Interestingly, we detected a correlation between constipation prevalence in PD patients and healthy control groups in individual studies, raising concerns about how various constipation questionnaires are implemented across study populations. More than 80% of PD patients exhibit prolonged colonic transit time, and the same is probably true for de novo PD patients. Thus, the prevalence of objective colonic dysfunction exceeds the prevalence of subjective constipation. Colonic transit time measures are simple, widely available, and hold promise as a useful biomarker in manifest PD. More research is needed to elucidate the role of gastrointestinal dysfunction in disease progression of PD. Moreover, colonic transit measures may have utility as a more accurate risk factor for predicting PD in the prodromal phase. © 2016 International Parkinson and Movement Disorder Society